2020
DOI: 10.1038/s41380-020-0677-9
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging genome-wide data to investigate differences between opioid use vs. opioid dependence in 41,176 individuals from the Psychiatric Genomics Consortium

Abstract: To provide novel insights into the biology of opioid dependence (OD) and opioid use (i.e., exposure, OE), we completed a genome-wide analysis comparing up to 4,503 OD cases, 4,173 opioid-exposed controls, and 32,500 opioid-unexposed controls. Among the variants identified, rs9291211 was associated with OE (a comparison of exposed vs. unexposed controls; z=-5.39, p=7.2×10 -8 ). This variant regulates the transcriptomic profiles of SLC30A9 and BEND4 in multiple brain tissues and was previously associated with de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
128
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 61 publications
5
128
2
Order By: Relevance
“…Several GWAS studies have evaluated opioid use disorder (OUD) and/or opioid dependence, and have identified a variety of loci including SNPs linked to OPRM1, KCNG2, CNIH3, LOC647946, LOC101927293, CREB1, PIK3C3, and RGMA 52 57 Additional human linkage studies have identified sex-specific traits 58 , epigenetic biomarkers 59 or copy number variations 60 for risk of OUD. Other studies have sought to separate opioid use from opioid dependence, and have thus far identified SNPs associated with SDCCAG8, SLC30A9, and BEND4 61 . Only one study has looked at human opioid overdose risk, specifically by scoring overdose status and determining the number of times that medical treatment was needed in European American populations 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Several GWAS studies have evaluated opioid use disorder (OUD) and/or opioid dependence, and have identified a variety of loci including SNPs linked to OPRM1, KCNG2, CNIH3, LOC647946, LOC101927293, CREB1, PIK3C3, and RGMA 52 57 Additional human linkage studies have identified sex-specific traits 58 , epigenetic biomarkers 59 or copy number variations 60 for risk of OUD. Other studies have sought to separate opioid use from opioid dependence, and have thus far identified SNPs associated with SDCCAG8, SLC30A9, and BEND4 61 . Only one study has looked at human opioid overdose risk, specifically by scoring overdose status and determining the number of times that medical treatment was needed in European American populations 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Additional human linkage studies have identified sex-specific traits 46 , epigenetic biomarkers 47 or copy number variations 48 for risk of OUD. Other studies have sought to separate opioid use from opioid dependence, and have thus far identified SNPs associated with SDCCAG8, SLC30A9, and BEND4 49 . Only one study has looked at human opioid overdose risk, specifically by scoring overdose status and determining the number of times that medical treatment was needed in European American populations 50 .…”
Section: Discussionmentioning
confidence: 99%
“…A GWAS on alcohol use disorder identified 18 genome-wide significant loci 2 . GWAS on opioid 3 or cocaine use disorders 4 have also been conducted or are ongoing.…”
Section: Introductionmentioning
confidence: 99%